Knowledge Acquisition in Toraja’s Local Wisdom Context Toward Sustainable Tourism Development - Ferdinandus Sampe (Jurnal Bisnis dan Kewirausahaan, 2020)
The tourism sector is spurred as a source of national income, a provider of employment and a means of equitable distribution of national income. As one of the tourist destinations, Tana Toraja Regency has also been managed to take advantage of existing tourism potential, such as natural beauty, distinctive culture and values ​​embraced by the Toraja people hospitality. To use the cultural heritage to boost the tourism business, all organizational members should acquire, elaborate and use all relevant information for decision making in tourism Micro, Small and Medium Enterprises (MSMEs). Data were collected using a set questionnaire hand-delivered to MSMEs owner/manager. As many as 50 questionnaires were distributed and 35 questionnaires were completed and then analyzed. The results reveal that MSMEs knowledge acquisition concerning their local wisdom and environment was above the middle range. It is suggested that a model of continuous learning by combining local wisdom and external knowledge.